The Effect of School Culture, and Emotional Quotient on Teacher’s Organizational Commitment in Senior High School in District of Padang Lawas - Aswin Bancin (Journal Mathematics Education Sigma [JMES], 2024)
This study aimed to determine: (1) the effect of school culture on teacher’s organizational commitment, and (2) the effect of emotional Quotient on teacher’s organizational commitment. This study uses quantitative methods, the model used is the path analysis with inferential data analysis techniques. The population in this study are all teachers of senior high school in the district of Padang Lawas, amounting to 214 teachers. The research sample was determined by using a proportional stratified random sampling technique to obtain a sample of 137 teachers. The research instrument used for data collection was a questionnaire. The results of this study found: (1) there is a direct and significant effect of school culture on teachers' organizational commitment with the R31 correlation coefficient = 0,233 with a contribution effect of 5% (2) there is a direct and significant influence of emotional intelligence on organizational commitment of teachers with a correlation coefficient R32 = 0,094 with contribution of the direct effect by 10%.